Organic matter compositions of rivers draining into Hudson Bay: Present‐day trends and potential as recorders of future climate change. Issue 7 (26th July 2017) - Godin, Pamela; Macdonald, Robie W.; Kuzyk, Zou Zou A.; Goñi, Miguel A.; Stern, Gary A.
Abstract: Concentrations and compositions of particulate and dissolved organic carbon (POC and DOC, respectively) and aromatic compounds including lignin were analyzed in water samples from 17 rivers flowing into Hudson Bay, northern Canada. These rivers incorporate basins to the south with no permafrost to basins in the north with continuous permafrost, and dominant vegetation systems that include Boreal Forest, the Hudson Plains, Taiga Shield, and Tundra. Major latitudinal trends in organic carbon and lignin concentrations and compositions were evident, with both DOC and dissolved lignin concentrations dominating over their particulate counterparts and exhibiting significant correlations with total dissolved and suspended solids, respectively. The composition of lignin reaction products in terms of the syringyl, cinnamyl, and vanillyl compositions indicate mixed sources of vascular land plant‐derived organic carbon, with woody gymnosperms contributions dominating in the southern river basins whereas nonwoody angiosperm sources were more important in the most northerly rivers. The composition of nonlignin aromatic compounds, which provides a tracer for nonvascular plant contributions, suggests stronger contributions from Sphagnum mosses to dissolved organic matter in rivers below the tree line, including those with large peat bogs in their basins. Acid/aldehyde ratios of the lignin products together with Δ 14 C data for DOC in selected rivers indicate that DOC has generally undergone greater alteration than POC. Interestingly, several northern rivers exhibited relatively old DOC according to the Δ 14 C data suggesting that either old DOC is being released from permafrost or old DOC survives river transport in these rivers. Key Points: Seventeen Hudson Bay rivers spanning a wide vegetative and permafrost range were sampled for DOC, POC, and lignin compositions Trends were distributed latitudinally, reflecting woody angiosperms in the south, nonwoody gymnosperms in the north There is evidence of release of DOC from soil permafrost based on fresh‐appearing aldehyde ratios coupled with depleted Δ 14 C activities Plain Language Summary: Dissolved and particulate compounds characteristic of plants have been examined at the outflows of 17 rivers entering Hudson Bay. The river basins, which occupy a wide expanse in latitude, range from no permafrost to complete permafrost, and a wide varied of vegetation types depending on the climate within the basins. The data clearly distinguish between rivers draining areas south of the treeline and those draining tundra to the north. Carbon‐14 data for DOC in 8 rivers suggests that old material is being released into several rivers including the most northerly. The baseline provided by these data should help to understand the rapid change this region is going through as warming thaws permafrost and promotes vegetation changes.